Alterações no aspecto confessional em dois colégios protestantes de educação básica na cidade de São Paulo (1978-2018) - Andrade, Jefferson Ricardo de (2019)
The research analyzed levels of maintenance or decline of the values religious that guide Protestant denominational institutions located in the city of São Paulo, whose procedures, comparatively, are traced by the quantitative increase in the number of students, considering specific historical periods. Two institutions were tested in the city of São Paulo: the College of the Adventist University Center and the Lutheran College. The documentary analysis (School Regiment, School Plan, among other auxiliary sources) aimed to check ruptures and permanence in the respective approaches of the two selected schools between 1978 and 2018. Methodological contributions were used in the History of Educational Institutions, such as: analysis of institutional genesis, organization, functioning, representations, tradition and memories, practices, involvement, appropriation, as well as those that privilege different confessionalities and their articulations with space, time and singularities. According to the information collected in the research, the two institutions, throughout their trajectories, school regiments, school plans, curriculum and bulletin of the school community, demonstrated the maintenance of religious confession, with varied appropriations, including the present moment, granting the reflection about the representations and reasoning of the confessional aspect of both colleges